Produksi Hidrogen dari Campuran Air dan Minyak Kelapa Murni (VCO) melalui Porous Media Tembaga menggunakan Prinsip Hydrogen Reformer - Putra, Bernardus Crisanto; Wardana, I.N.G.; Siswanto, Eko (Rekayasa Mesin, 2016)
Hydrogen reformer is a principle of hydrogen formation by using the reaction between reactants with a catalyst and a heating process in vapor form. Copper powder was used as the catalyst with a porosity of 28.245% and 31.736%, and a heat temperature of 310 oC. Variation of the ratio between water and virgin coconut oil (VCO) mixture of 1:1, 1:2, 1:3, 1:4 and 1:5 was developed to investigate the hydrogen generated productivity. The images of burning flame was taken at the outlet pipe of steam reaction to indicate the productivity of the hydrogen. The results shown that the productivity of the hydrogen was obtained by calculating the images of flame colors. The images indicate that the productivity of the hydrogen increase with adding virgin coconut oil (VCO) to water is greater. The average amount of energy and the power needed to react all variations on a comparison of hydrogen reformer tube 5 are 53.53885 kJ and 0.18666 kJ/sec, respectively.